Observation of the associated production of a top quark and a Z boson in pp collisions at √s=13 TeV with the ATLAS detector - Aad, Georges; Anders, Christoph; Andrei, George Victor; Bolz, Arthur; Dunford, Monica; Ferreira de Lima, Danilo Enoque; Franchino, Silvia; Helary, Louis; Jongmanns, Jan; Klassen, Martin; Krishnan, Anjali; Kugel, Andreas; et al. (Journal of high energy physics, 2020)
Single top-quark production in association with a Z boson, where the Z boson decays to a pair of charged leptons, is measured in the trilepton channel. The proton-proton collision data collected by the ATLAS experiment from 2015 to 2018 at a centre-of-mass energy of 13 TeV are used, corresponding to an integrated luminosity of 139 fb−1. Events containing three isolated charged leptons (electrons or muons) and two or three jets, one of which is identified as containing a b-hadron, are selected. The main backgrounds are from tt¯Z and diboson production. Neural networks are used to improve the background rejection and extract the signal. The measured cross-section for tℓ+ℓ−q production, including non-resonant dilepton pairs with mℓ+ℓ− > 30 GeV, is 97 ± 13 (stat.) ± 7 (syst.) fb, consistent with the Standard Model prediction.
ATLAS Collaboration: G. Aad, C. Anders, G.V. Andrei, A. Bolz, M. Dunford, D.E. Ferreira de Lima, S. Franchino, L. Helary, J. Jongmanns, M. Klassen, M. Kolb, A. Krishnan, A. Kugel, M. Lisovyi, T. Mkrtchyan, F. Napolitano, P. Ott, M. Sahinsoy, A. Schoening, H.-C. Schultz-Coulon, T. Spieker, R. Stamen, P. Starovoitov, S. Suchek, L. Vigani, S. Weber, M. Wessels, X. Yue [und 2894 weitere]
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
Gesehen am 05.11.2020